2020
DOI: 10.1016/j.ijwd.2020.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Stevens-Johnson syndrome and toxic epidermal necrolysis in pregnant patients: A systematic review

Abstract: Background Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are two of the most severe dermatologic emergencies. Although pregnant women comprise a subset of individuals at risk for SJS and TEN development, little is known with regard to outcomes and treatment. Objective This study aimed to conduct a systematic review to characterize the risk factors, outcomes, and treatment of SJS and TEN in pregnant patients and newborns. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“… 4 Although no randomized controlled trials exist for its use during pregnancy, it has a short half-life, and studies demonstrate that there is low transplacental transfer of etanercept in the third trimester 5 ; however, there are no published data regarding its use for the treatment of SJS in pregnant patients. 6 …”
Section: Discussionmentioning
confidence: 99%
“… 4 Although no randomized controlled trials exist for its use during pregnancy, it has a short half-life, and studies demonstrate that there is low transplacental transfer of etanercept in the third trimester 5 ; however, there are no published data regarding its use for the treatment of SJS in pregnant patients. 6 …”
Section: Discussionmentioning
confidence: 99%
“…Jika vagina terlibat, akan muncul erosi vagina dengan keputihan bernoda darah dan bernanah. 27 Erosi vagina dapat menyebabkan sinekia vagina, aglutinasi vulva, stenosis, atau oklusi vagina. Gejala sisa akibat oklusi vagina termasuk hematokolpos, hematometra, dan endometriosis.…”
Section: Komplikasi Gastrointestinalunclassified
“…Tanpa pengobatan, waktu penyembuhan lesi vulvovaginal berkisar antara 7 hingga 56 hari. 26,27 Penyintas SSJ/NET dengan gejala atau lesi ginekologi persisten harus menjalani biopsi punch pada vulva dan vagina serta observasi ketat dengan kolposkopi jika biopsi positif untuk adenosis vulvovaginal, adenosis vulvovaginal memiliki potensi berubah menjadi sel skuamosa dan karsinoma sel bening pada vagina. 28…”
Section: Komplikasi Gastrointestinalunclassified
“…A meta-analysis reported an incidence of skin rash with lamotrigine of almost 10% of persons from prospective studies [63] from high-income countries (HIC). Similarly, a recent review suggested that HAART, being implicated in 90% of cases, constitutes the most common putative medications in pregnant women [64].…”
Section: Sjs/tenmentioning
confidence: 99%